Multikulturalisme dan Dinamika Sosial Lansia di Panti Jompo Yayasan Netizen Cinta Singkawang (Studi Kasus) - Rizky Septia Utami Bafadal; Dita Pratiwi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This qualitative case study examines the implementation of multiculturalism and social dynamics among the elderly at the Netizen Cinta Singkawang Nursing Home Foundation in Indonesia. Data were collected through in-depth interviews with the founder of the nursing home and an analysis of transcript documents. The analysis was guided by Parsudi Suparlan's Theory of Multiculturalism and Herbert Blumer's Theory of Symbolic Interactionism. The findings reveal that multiculturalism is practiced through inclusive policies that prioritize the value of humanity, the accommodation of halal dietary needs for all residents, and the celebration of major religious holidays. Social dynamics are characterized by harmonious daily interactions, the formation of a collective identity as a